THE ROLE OF THROUGHPUT ACCOUNTING TECHNIQUE IN COST MANAGEMENT-AN APPLIED STUDY IN AL-NARJIS PIPE MANUFACTURING COMPANY - Jaber Hussein Ali Al-Mansori; Batool Abd A. D. Al-Mansori (Scholar Express Journals, 2025)
In light of the transformations witnessed in the contemporary business environment, cost accounting systems must adapt to ongoing changes in order to manage scarce resources, address bottlenecks, and overcome production constraints. Throughput Accounting (TA) is one of the modern approaches based on the Theory of Constraints (TOC) as a foundation for developing and improving cost accounting systems. This study derives its importance from TA’s ability to address the negative effects of resource misutilization, especially under constrained operations, which often leads to lower output quality and productivity. Many companies, especially in Iraq, seek to overcome the constraints impeding production continuity and process flow. By adopting TA, these companies aim to improve operational performance, reduce costs, and enhance productivity Moreover, this approach provides practical solutions to bottlenecks that limit the efficiency and effectiveness of operational processes, enabling organizations to remain competitive in a rapidly changing market. The objective of this study is to highlight the role of Throughput Accounting as a tool for developing cost accounting systems in the modern manufacturing environment, to manage costs more efficiently. The findings indicate that the information provided by TA plays a significant role in measuring and managing costs. It also supports planning and control processes by maximizing throughput and reducing inventory levels.
Keywords: Throughput Accounting; Cost Management.